Labour Consumption of Production of Selected Fruit (Agricultural Engineering, 2018)
The objective of the paper was to analyse the expenditures of labour in production of three selected fruit types (apples, black currant and gooseberry) including, inter alia, in relation to the surface area of a plantation. The total inputs of labour were calculated with a division into manual and mechanized works. Moreover, a detailed structure of manual and mechanized works was presented. It was stated, inter alia, that labour consumption of apple production is approximately four times higher in comparison to black currant and gooseberry. No impact of the plantation size on the total work inputs on fruit production was reported.